Analisis Kebutuhan Pelatihan Medik Veteriner Provinsi Riau - Melfianora Melfianora (Jurnal Kewidyaiswaraan, 2019)
Section or division jobs which is handling technic in animal health are almost the same as vets of veterinary. If there were any available trainings and educations, they were attended by structural officials in that section division. So vets of veterinary which are at remote area had little chance to attend courses. That is why and in knowing the fit trainings and educations for Riau vets of veterinary, it is needed to hold training need analysis for vets of veterinary. The purpose of this research is to idetificate competency or training needs of vets of veterinary. Research methods and techniques are Focus Group and Nominatif Group and DIF (Difficuties, Importancy, Frequency) Technique. Analysis gives 15 training and eduction for vets of veterinary.